2012
DOI: 10.1016/j.physbeh.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 decreases amphetamine-induced locomotor activity

Abstract: Glucagon-like peptide-1 (GLP-1) is released in response to nutrient ingestion and is a regulator of energy metabolism and consummatory behaviors through both peripheral and central mechanisms. The GLP-1 receptor (GLP-1R) is widely distributed in the central nervous system, however little is known about how GLP-1Rs regulate ambulatory behavior. The abused psychostimulant amphetamine (AMPH) promotes behavioral locomotor activity primarily by inducing the release of the neurotransmitter dopamine. Here, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 66 publications
5
60
0
Order By: Relevance
“…Similar finding were reported in rats where the locomotor response precipitated by the psycho stimulant amphetamine was modulated by the administration of GLP-1 [7]. These findings have not yet been replicated in humans.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar finding were reported in rats where the locomotor response precipitated by the psycho stimulant amphetamine was modulated by the administration of GLP-1 [7]. These findings have not yet been replicated in humans.…”
Section: Introductionsupporting
confidence: 78%
“…The LEAD-3 study attributed non-significant improvements in anxiety to globally increased satisfaction with improved glycaemic control and weight reduction, rather than to a central effect of the GLP-1 analogue per se [11]. Given the evidence from animal studies of GLP-1-induced reduction in alcohol intake and in the modulation of the locomotor response precipitated by amphetamine indicates that the reward centres (mesolimbic pathway) may have a role in this effect [6,7]. Further evidence of central action of exenatide in fMRI studies [13], supports this: although the exact mechanism whereby GLP-1 mediates an effect on anxiety remains unclear, it is likely to be associated with receptors in the mesolimbic system.…”
Section: Discussionmentioning
confidence: 99%
“…Liraglutide was not detected outside of CVOs and hypothalamus, so the activation in these areas except AP may be indirect. There likely are important effects of GLP-1R in areas of the brain associated with reward, as GLP-1R agonists have been show to lead to changed food preference away from typically rewarding foods (79), and exendin-4 has been shown to reduce basal as well as amphetamine-induced locomotor activity, and reduced alcohol intake has also been reported (80,81).…”
Section: Surgery Models and Compound Administrationmentioning
confidence: 99%
“…Given that the limbic system is central for the rewarding properties of behavior, substances, and food (59), this is hardly surprising. In fact, several studies have concluded that activation of GLP-1R in the limbic system can attenuate the reward from the consumption of cocaine (19,27) or amphetamines (19,21), and even lead to reduced consumption of narcotics, such as alcohol (20,88). These observations also go hand in hand with the presence of GLP-1 receptor mRNA (65) and PPG projections to the VTA, bed nucleus of the stria terminalis (BNST), amygdala, NAc, and lateral septum (LS).…”
Section: Brain Glp-1 and Food Intakementioning
confidence: 99%